Rypoš lysý a myš domácí jako modelové organismy reprodukčního stárnutí - Kopecká, Eva (Jihočeská univerzita, 2021)
The aim of this study is to demonstrate the naked mole rat as a new possible model of reproductive aging. It is also pointing out the reproductive problems and diseases associated with increasing age in women. Furthermore, the study wants to introduce the role of mTOR in mouse embryonic development in relation to maternal age and decrease in fertility in a view of number of oocytes in mouse, guinea pig and naked mole rat.
The naked mole rat and the house mouse as model organisms of reproductive aging
Keywords: myš domácí (Mus musculus); rypoš lysý (Heterocephalus glaber); morče domácí (Cavia porcellus); preimplantační vývoj; 16- buňkové stádium; mTOR signalizační dráha; reprodukční stárnutí; oocyt; embryo